Alice in Borderland. Volume 9 - Aso, Haro, 1980- (Viz signature., 2024)
"After stumbling on a dealer's bunker, Arisu is even more determined to uncover the terrible truth behind Borderland. But that means he and Usagi will have to abandon their plans to sit out the games and instead seek out the last person who might have the answers--the Queen of Hearts. Will taking on the queen find them a way home, or will it be their final game?"--Back cover.